SIN3A Regulates Porcine Early Embryonic Development by Modulating CCNB1 Expression - Luo, Lei; Dang, Yanna; Shi, Yan; Zhao, Panpan; Zhang, Yunhai; Zhang, Kun (Frontiers in Cell and Developmental Biology, 2021)
SIN3A is the central scaffold protein of the SIN3/histone deacetylase (HDAC) transcriptional repressor complex. SIN3A participates in the mouse preimplantation development by finetuning HDAC1 expression. However, it remains unresolved if this functional significance of SIN3A was conserved in other mammals. Herein, RNA-seq results show a large amount of SIN3A mRNA is present in oocytes and early embryos prior to embryonic genome activation and a low amount thereafter, suggesting a maternal origin of SIN3A in all species examined. Interestingly, immunofluorescence data show that SIN3A protein level peaks at 4-cell stage in pigs compared with morula stage in cattle. SIN3A depletion in early embryos causes a developmental arrest at 2-cell stage in pigs but does not affect bovine early embryonic development. In contrast with mouse data, SIN3A depletion results in only a slight decrease and even no difference in HDAC1 expression in porcine and bovine early embryos, respectively. In addition, HDAC1 knockdown does not cause 2-cell block, but leads to a reduced blastocyst rate. By using un-biased RNA-seq approach, we found that Cyclin B1 (CCNB1) transcript level is dramatically reduced. Moreover, CCNB1 knockdown results in a similar phenotype as SIN3A depletion. Injection of exogenous CCNB1 mRNA into SIN3A-depleted embryos could partly rescue embryonic development to pass 2-cell stage. In conclusion, our results indicate SIN3A plays an essential role in porcine early embryonic development, which probably involving the regulation of CCNB1 expression.